Use of molecular biomarkers to estimate manganese requirements for broiler chickens from 22 to 42 d of age. Issue 9 (4th November 2016) - Lu, Lin; Chang, Bin; Liao, Xiudong; Wang, Runlian; Zhang, Liyang; Luo, Xugang
Abstract: The present study was carried out to evaluate dietary Mn requirements of broilers from 22 to 42 d of age using molecular biomarkers. Chickens were fed a conventional basal maize–soyabean meal diet supplemented with Mn as Mn sulphate in graded concentrations of 20 mg Mn/kg from 0 to 140 mg Mn/kg of diet for 21 d (from 22 to 42 d of age). The Mn response curves were fitted for ten parameters including heart Mn-containing superoxide dismutase (MnSOD) mRNA and its protein expression levels and the DNA-binding activities of specificity protein 1 (Sp1) and activating protein-2 (AP-2). Heart MnSOD mRNA and protein expression levels showed significant quadratic responses ( P <0·01), and heart MnSOD activity showed a broken-line response ( P <0·01), whereas Mn content and DNA-binding activities of Sp1 and AP-2 in the heart displayed linear responses ( P <0·01) to dietary Mn concentrations, respectively. The estimates of dietary Mn requirements were 101, 104 and 94 mg/kg for full expressions of MnSOD mRNA level, MnSOD protein level and MnSOD activity in the heart, respectively. Our findings indicate that heart MnSOD mRNA expression level is a more reliable indicator than heart MnSOD protein expression level and its activity for the evaluation of Mn requirement of broilers, and about 100 mg Mn/kg of diet is required for the full expression of heart MnSOD in broilers fed the conventional basal maize–soyabean meal diet from 22 to 42 d of age.